2021
DOI: 10.3390/ijms22052709
|View full text |Cite
|
Sign up to set email alerts
|

P25 Gene Knockout Contributes to Human Epidermal Growth Factor Production in Transgenic Silkworms

Abstract: Transgenic silkworm expression systems have been applied for producing various recombinant proteins. Knocking out or downregulating an endogenous silk protein is considered a viable strategy for improving the ability of transgenic expression systems to produce exogenous proteins. Here, we report the expression of human epidermal growth factor (hEGF) in a P25 gene knockout silkworm. The hEGF gene regulated by the P25 gene promoter was integrated into a silkworm’s genome. Five transgenic positive silkworm lineag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…2 ). We demonstrated that P25, a major component of the ancient cocoon silk structure, is substitutable, as also demonstrated by a recent report of knocking out the P25 coding gene in Bombyx mori 8 , 33 . P25 is a glycoprotein containing Asn-linked oligosaccharide chains that forms a compact structure because of intramolecular disulfide linkages but associates with the H–L complex through non-covalent interactions 34 .…”
Section: Discussionsupporting
confidence: 83%
“…2 ). We demonstrated that P25, a major component of the ancient cocoon silk structure, is substitutable, as also demonstrated by a recent report of knocking out the P25 coding gene in Bombyx mori 8 , 33 . P25 is a glycoprotein containing Asn-linked oligosaccharide chains that forms a compact structure because of intramolecular disulfide linkages but associates with the H–L complex through non-covalent interactions 34 .…”
Section: Discussionsupporting
confidence: 83%
“…Proteins were extracted according to a previously described method with some modifications ( Wu et al, 2021 ). Briefly, silk gland and cocoon shell proteins were extracted with sodium dodecyl sulfate (SDS) buffer (1:40, wt/vol) containing 5% (vol/vol) β-mercaptoethanol, and the supernatants were collected by centrifuging after incubation at 37 °C for 8 h. The extracted proteins were quantified using a Modified BCA Protein Assay Kit (Sangon Biotech); then, western blotting analysis was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Expression systems based on FibH, FibL, and ser1 promoters were often used because they could express relatively high levels of exogenous proteins ( Xu, 2014 ). Since 2003, when the FibL promoter was first used to specifically express recombinant proteins in silkworm silk glands via piggyBac transposon-mediated transgenes ( Tomita et al, 2003 ), the production of recombinant proteins using transgenic silkworm silk gland bioreactors has entered a period of rapid development ( Long et al, 2021 ; Wu et al, 2021 ; Chen et al, 2022 ). In addition, modification of piggyBac transposon-based transgene regulatory elements has been found to improve the expression levels of exogenous proteins ( Iizuka et al, 2008 ; Zhao et al, 2021 ), and a recent study showed that the use of native regulatory elements could increase the production of exogenous proteins up to 15-fold compared with an artificially truncated promoter ( Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that production of human epidermal growth factor (hEGF) of about 8 kDa at 2.2 times higher amounts than normal silkworms was also possible by knocking out the P25 gene in silkworms. Modified silkworms were similar in appearance and produced fibers with same properties compared to cocoons obtained from unmodified silkworms (Wu et al, 2021). Increase in production of exogenous proteins by knocking out endogenous proteins such as P25 were suggested to be viable approaches for large scale production of proteins and proteins containing biomolecules.…”
Section: Production Of Growth Factors By Transgenic Silkwormsmentioning
confidence: 99%